White Place, general view of a private residence, Brookline, Massachusetts, 10 of 21. - Floyd, Margaret Henderson. (Tufts University. Tisch Library., 2015)
General exterior view of a building in the White Place area of Brookline, Massachusetts. One of several slides taken in this area.; Caption on image: White Place (2) Gen. view of area.; Binder Number 4. Pocket Number: 16.; Format: 35mm col. slide.; Slide created date: This date is approximate. 1978.; Apply to the DCA for access to the physical slides.